Community Empowerment of the Musi River Estuary Coastal Area (Marga Sungsang Village) in Meeting Clean Water Needs through a Simple Raw Water Treatment Plant - Melki Melki; Wike Ayu Eka Putri; Isnaini Isnaini; Hartoni Hartoni; Jeni Meiyerani (Universitas Muhammadiyah Palembang, 2024)
Community empowerment in the coastal area of the Musi River Estuary is one of the important efforts to improve the quality of life and welfare of the surrounding community. The main obstacle faced by coastal communities is limited access to clean water that meets health standards. This activity aims to identify the application of simple technology in raw water treatment to meet the needs of clean water in the coastal area of the Musi River Estuary. Through a simple raw water treatment plant (IPAB), the community is involved in every stage, from planning to denationalization, by providing training and technical assistance. The results of the application of this technology show that simple raw water treatment plants are able to improve water quality and meet clean water needs at a more efficient cost than conventional technology. In addition, community empowerment in the management of this installation also increases awareness of the importance of cleanliness and sustainability of water resources. Overall, this initiative has had a positive impact in improving access to clean water for coastal communities, as well as being a model that can be applied in other coastal areas with similar conditions.